Thermal ice pressure on structures in ice covers - Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 1988)
A method to estimate thermal ice pressure is proposed. Temperature-history and stress-history in a confined ice sheet heated at the surface is illustrated with numerical examples. Material parameters for columnar lake ice has been evaluated from classical laboratory experiments and a field program presented here. A Young´s modulus of 5 GPa was obtained from pressure measurements in a well confined and uncracked ice sheet. Godkänd; 1988; 20070424 (ysko)